The Aristotelian Theos in Hegel's Philosophy of mind - Plevrakis, Ermylos (Hegel bulletin, 2020)
Although Hegel does not pass up the opportunity to express his deep admiration for specific aspects of the Aristotelian notion of God, he is not interested in giving a concrete account of its systematic significance for his Philosophy of Mind as a whole. In this article, I seek to take an overarching perspective on both the Aristotelian God and the Hegelian mind. By contrast to the common practice of focusing on Hegel's interpretation of Aristotle in his Lectures on the History of Philosophy, I first examine the Aristotelian text itself and then focus on Hegel's Encyclopaedia Philosophy of Mind, in order to explore the coincidence between the two conceptions from a systematic point of view. With regard to Aristotle, I argue that ‘God’ represents the conceptual vanishing point of his philosophy at which all philosophical sciences appear to converge. With regard to Hegel, I show that it is precisely such conceptual convergence of all philosophical sciences that constitutes both the starting and ending points of the Philosophy of Mind. The result is a novel meta-scientific and non-theistic conception of ‘God’ that provides the means not only to re-evaluate the systematic relation between Hegel and Aristotle but also to reconsider the character, content and aim of speculative philosophy in general.